Identification of superior parents and hybrids for yield improvement in castor (Ricinus communis L.): IDENTIFICATION OF SUPERIOR PARENTS AND HYBRIDS FOR YIELD IMPROVEMENT IN CASTOR - YAMANURA; R MOHAN KUMAR; C LAVANYA; S SENTHILVEL (Journal of Oilseeds Research, 2020)
An experiment was conducted to determine the nature and magnitude of heterosis in castor for seed yield and its yield attributing traits. Forty hybrids were synthesized involving five lines and eight testers through line x tester (L×T) mating design and were evaluated for yield and its components. Among 13 parental lines, JP-96, VP-1, DPC-9, RG-2661-1, RG-109 and RG-3160 were identified as good general combiners for seed yield and its components, which can be directly exploited in heterosis breeding. The cross combination, DPC-18 × RG-2661-1 was good specific combiner for early maturity. High seed yield per plant was recorded for hybrids: VP-1×RG-109 (105.04 g), DPC-18×RG-1771 (98.26g) and DPC-18×RG-2661-1 (97.97 g). These promising crosses involved parents with high × high and high × low GCA effects and were found promising for high yield potential in castor.